A journey of embedding mental health lived experience in social work education. Issue 8 (16th November 2016) - Dorozenko, Kate P.; Ridley, Sophie; Martin, Robyn; Mahboub, Lyn
Abstract: The value of learning from mental health lived experience is widely acknowledged, however, the nature of lived experience involvement in Australian social work education seldom extends beyond guest lecturing. Further, few opportunities exist that build the capacity of people with lived experience to become educators within tertiary settings. In this paper we present the Valuing Lived Experience Project (VLEP), an initiative led by a Lived Experience Academic (LEA) that seeks to systematically and meaningfully embed lived experience into the social work curriculum at a Western Australian university by providing significant opportunities for the capacity building of both individuals with mental health lived experience and academics. Given the relative infancy of service user involvement in Australian social work education, the VLEP offers a number of opportunities for reflection and consideration. A long-standing partnership between a LEA and Social Work Academic is described, the activities and key learnings of the VLEP to date are outlined, and we offer our reflections on challenges encountered throughout the journey. We hope that our experiences and learnings can be drawn upon to progress lived experience participation in tertiary settings and further legitimise lived experience involvement in the education of social workers.